Au-incorporated NiO nanocomposite thin films as electrochromic electrodes for supercapacitors. (10th January 2020) - Jung, Hyun Kyu; Lee, Sang Jin; Han, Dongwook; Hong, A-Ra; Jang, Ho Seong; Lee, Seung Han; Mun, Jeong Heum; Lee, HanJin; Han, Seung Ho; Yang, Daejin; Kim, Dong Hun
Abstract: Herein, we reported a facile synthesis of nanocomposite thin films containing Au nanoparticles within a NiO matrix using a simple and low-cost deposition apparatus. Au nanoparticle contents were controlled by changing the exposed areas of the nickel foil on the Au foil during sputtering. Surface plasmon resonance peaks were observed in the absorption spectrum, indicating that nano-sized Au particles were formed in the NiO matrix, which was also confirmed by electron microscopy and X-ray photoelectron spectroscopy. Highly conductive Au nanoparticles in NiO improved the electrical conductivity, and the Au-incorporated NiO nanocomposite thin film electrode exhibited greatly enhanced pseudo-capacitive property with a 1.5 times higher specific capacity than that of the pure NiO electrode even if it is not totally capacitive. This study provides a novel and facile method for the direct preparation of metal nanoparticles embedded in oxide nanocomposite films, which will offer exciting opportunities in supercapacitors. In addition, the prepared electrodes showed enhanced electrochromic capabilities and coloration efficiency, suggesting their potential for application in electrochromic smart glass monitoring by color change for energy storage.